Dynamic phosphorylation of apoptosis signal regulating kinase 1 (ASK1) in response to oxidative and electrophilic stress - Betanzos, Carlos Morales (Chem Res Toxicol, 2016)
Apoptosis signal-regulating kinase 1 (ASK1) is a critical cellular stress sensor that senses diverse reactive chemotypes and integrates these chemical signals into a single biological pathway response. It is unknown whether ASK1 senses all stressors in the same way, or if unique stress-specific mechanisms detect distinct chemotypes. In order to answer this question, we treated ASK1-expressing cells with two distinct stress activators, H(2)O(2) and 4-hydroxy-2-nonenal (HNE), and monitored the phosphorylation state of ASK1. Phosphorylation is an important regulator for the activity of ASK1 and we hypothesized that these two chemically distinct molecules may produce differences in the phosphorylation state of ASK1. Shotgun mass spectrometry and manual validation identified 12 distinct ASK1 phosphosites. Targeted parallel reaction monitoring assays were used to track the phosphorylation dynamics of each confirmed site in response to treatment. Eleven phosphosites exhibited dynamic response to one or both treatments. Six of these sites were identified in both H(2)O(2) and HNE treated cells and four of these exhibited a consistent response between the two molecules. The results confirm that different chemotypes produce distinct phosphorylation patterns in concert with activation of a common MAPK pathway.